O Princípio da Preocupação: Perspectivas de Aplicação no Âmbito Ambiental e Penal - Nobre, Márcio Albuquerque; Martins, Fernanda Gonçalves Galhego (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2015)
This study analyses the contribution of the new basic law on environment to the implementation of the precautionary principle in the context of environmental law and assesses the possibility of implementing this principle in the criminal law.